2020
DOI: 10.1080/23311886.2020.1718578
|View full text |Cite
|
Sign up to set email alerts
|

Analysis and study of hospital communication via social media from the patient perspective

Abstract: Currently, the online interaction between citizens and hospitals is poor, as users believe that there are shortcomings that could be improved. This study analyzes patients' opinions of the online communication strategies of hospitals in Spain. Therefore, a mixed-method is proposed. Firstly, a qualitative analysis through a focus-group was carried out, so around twenty representatives of national, regional and local patients' associations were brought together. Secondly, the research is supplemented with a cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 55 publications
0
18
0
1
Order By: Relevance
“…34 This may result in larger utilization of social media platforms with more frequent posts than respective vascular programs, who may not have an independent marketing budget. Additionally, the availability of hospitals to use topic content from multiple medical specialties for posts covering fundraisers, news, health promotion, and research breakthroughs 35 may enable a larger quantity of posts and therefore higher activity, in comparison to vascular surgery programs. Furthermore, less social media utilization by vascular surgery in comparison to general surgery could be a reflection of the lower numbers of vascular surgeons than general surgeons overall.…”
Section: Discussionmentioning
confidence: 99%
“…34 This may result in larger utilization of social media platforms with more frequent posts than respective vascular programs, who may not have an independent marketing budget. Additionally, the availability of hospitals to use topic content from multiple medical specialties for posts covering fundraisers, news, health promotion, and research breakthroughs 35 may enable a larger quantity of posts and therefore higher activity, in comparison to vascular surgery programs. Furthermore, less social media utilization by vascular surgery in comparison to general surgery could be a reflection of the lower numbers of vascular surgeons than general surgeons overall.…”
Section: Discussionmentioning
confidence: 99%
“…In the USA, more than 95% of the top-ranked hospitals use social media as a corporate communication tool. Most patients appreciate these platforms as a source of medical information and emotional support, even if they sometimes complain about the technical language used by health professionals (De-las-Heras-Pedrosa et al, 2020).…”
Section: Cancer Hospitals' Corporate Communicationmentioning
confidence: 99%
“…Moreover, the use of social media has also changed how patients approach cancer treatments and what they think about cancer hospitals (Attai et al, 2016). Nevertheless, some patients have identified various barriers that stop them from utilizing social media, such as technical concepts related to cancer treatments or protocols applied in hospitals (De-las-Heras-Pedrosa et al, 2020). Regardless of this content, many patients have learned to convey their emotions better through social media, especially positive emotions such as hope, joy, or humor (Cho et al, 2018).…”
Section: Corporate Communication With Cancer Patients Through Social Mediamentioning
confidence: 99%
“…Thackeray, Neiger, Smith and Van Wagenen (2012) observed that public health agencies were unable to manage their social media in an interactive way and with the commitment of users. It has also been confirmed that Internet users are thankful towards hospitals for the effort of posting information through their social media, but in addition to lack of interaction, some messages are difficult to understand and some publications give a biased image (De Las Heras-Pedrosa, Rando-Cueto, Jambrino-Maldonado & Paniagua-Rojano, 2020). Busto-Salinas (2019), comparing the presence and activity on social media of different health-related organizations, observed that hospitals achieved greater interaction, despite they showed less assiduity and activity than other Will better performing health-care services have higher profiles and be more active on social media?…”
Section: Introduction and State Of The Questionmentioning
confidence: 96%